2016
DOI: 10.1002/ptr.5577
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Banaba–Moringa oleifera–Green Coffee Bean Extracts and Vitamin D3 in a Sustained Release Weight Management Supplement

Abstract: This 60‐day, 30‐subject pilot study examined a novel combination of ingredients in a unique sustained release (Carbopol matrix) tablet consumed twice daily. The product was composed of extracts of banaba leaf, green coffee bean, and Moringa oleifera leaf and vitamin D3. Safety was assessed using a 45‐measurement blood chemistry panel, an 86‐item self‐reported Quality of Life Inventory, bone mineral density, and cardiovascular changes. Efficacy was assessed by calculating a body composition improvement index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ethanolic and methanolic flowers and leaves extract of banaba were shown to have hepatoprotective properties. EBLE has an antiproliferative effect in cancer cell lines (Rohit Singh & Ezhilarasan, 2020; Thakur & Devaraj, 2020) and is also shown to have beneficial antifibrotic effects against carbon tetrachloride‐induced hepatotoxicity in Wistar rats (Stohs et al., 2016; Tiwari et al., 2017). To date, hepatoprotective evaluation of EBLE against the combined administration of INH + DDS‐induced hepatotoxicity has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanolic and methanolic flowers and leaves extract of banaba were shown to have hepatoprotective properties. EBLE has an antiproliferative effect in cancer cell lines (Rohit Singh & Ezhilarasan, 2020; Thakur & Devaraj, 2020) and is also shown to have beneficial antifibrotic effects against carbon tetrachloride‐induced hepatotoxicity in Wistar rats (Stohs et al., 2016; Tiwari et al., 2017). To date, hepatoprotective evaluation of EBLE against the combined administration of INH + DDS‐induced hepatotoxicity has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey on these herbal constituents revealed that an article had been published about the effect of African mango seeds on growth and lipid metabolism of young rats Wistar species 8 and its effect on overweight and obesity 9 . Green coffee seeds extracts has been cited in many articles as a weight loss supplement 10 , also raspberry has been cited as anti-obesity 11 .…”
mentioning
confidence: 99%